2005
DOI: 10.1007/bf02835740
|View full text |Cite
|
Sign up to set email alerts
|

Two-year observation of the clinical efficacy in treating chronic hepatitis B patients with Ganxian recipe and lamivudine

Abstract: GXR could inhibit the appearance of YMDD after long-term application of LVD, and combined use has marked synergism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Among these included studies, a study recruited schistosomiasis japonica patients only [20], the remaining recruited patients with chronic HBV infection. All of the identified studies were conducted in China and published in Chinese language, and only one study was published in English language [21]. Three studies used three-arm study design (2 intervention groups compared with 1 control group, or 1 intervention group compared with 2 control groups) [21-23] and others used two-arm study design (1 intervention group versus 1 control group) [20,24-42].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these included studies, a study recruited schistosomiasis japonica patients only [20], the remaining recruited patients with chronic HBV infection. All of the identified studies were conducted in China and published in Chinese language, and only one study was published in English language [21]. Three studies used three-arm study design (2 intervention groups compared with 1 control group, or 1 intervention group compared with 2 control groups) [21-23] and others used two-arm study design (1 intervention group versus 1 control group) [20,24-42].…”
Section: Resultsmentioning
confidence: 99%
“…All of the identified studies were conducted in China and published in Chinese language, and only one study was published in English language [21]. Three studies used three-arm study design (2 intervention groups compared with 1 control group, or 1 intervention group compared with 2 control groups) [21-23] and others used two-arm study design (1 intervention group versus 1 control group) [20,24-42]. No study reported mortality, liver cirrhosis or cancer, quality of life or cost as outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations